Mengoptimalkan Potensi UMKM Lokal melalui Pelatihan Ekonomi Digital di Desa Kotaraja, Lombok Timur - Salim, Sujiwa; Rahman, Arif (Lembaga Publikasi Ilmiah Nusantara, 2025)
Digital economy training is an essential step in empowering Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, particularly in rural areas. Kotaraja Village, located in East Lombok, is one such region with high MSME potential and requires innovative approaches to develop and market its local products. Through digital economy training, MSME actors are expected to optimize the use of digital technology to expand their markets, improve operational efficiency, and develop more effective marketing strategies.This training program covers the basics of online marketing, the use of e-commerce platforms, and the utilization of social media as tools to enhance the visibility and competitiveness of local products. Thus, it is hoped that MSMEs in Kotaraja Village will grow, become self-reliant, and compete in broader markets—both locally and globally—through the appropriate use of digital technology.